IPEM Topical Report: an international IPEM survey of MRI use for external beam radiotherapy treatment planning. (23rd March 2021) - Speight, Richard; Tyyger, Marcus; Schmidt, Maria A; Liney, Gary; Johnstone, Robert; Eccles, Cynthia L; Dubec, Michael; George, Ben; Henry, Ann; Herbert, Trina; Nyholm, Tufve; Mahmood, Faisal; et al.
Abstract: Introduction/Background . Despite growing interest in magnetic resonance imaging (MRI), integration in external beam radiotherapy (EBRT) treatment planning uptake varies globally. In order to understand the current international landscape of MRI in EBRT a survey has been performed in 11 countries. This work reports on differences and common themes identified. Methods . A multi-disciplinary Institute of Physics and Engineering in Medicine working party modified a survey previously used in the UK to understand current practice using MRI for EBRT treatment planning, investigate how MRI is currently used and managed as well as identify knowledge gaps. It was distributed electronically within 11 countries: Australia, Belgium, Denmark, Finland, France, Italy, the Netherlands, New Zealand, Sweden, the UK and the USA. Results . The survey response rate within the USA was <1% and hence these results omitted from the analysis. In the other 10 countries the survey had a median response rate of 77% per country. Direct MRI access, defined as either having a dedicated MRI scanner for radiotherapy (RT) or access to a radiology MRI scanner, varied between countries. France, Italy and the UK reported the lowest direct MRI access rates and all other countries reported direct access in ≥82% of centres. Whilst ≥83% of centres in Denmark and Sweden reported having dedicated MRI scanners for EBRT, all other countries reported ≤29%. Anatomical sites receiving MRI for EBRT varied between countries with brain, prostate, head and neck being most common. Commissioning and QA of image registration and MRI scanners varied greatly, as did MRI sequences performed, staffing models and training given to different staff groups. The lack of financial reimbursement for MR was a consistent barrier for MRI implementation for RT for all countries and MR access was a reported important barrier for all countries except Sweden and Denmark. Conclusion . No country has a comprehensive approach for MR in EBRT adoption and financial barriers are present worldwide. Variations between countries in practice, equipment, staffing models, training, QA and MRI sequences have been identified, and are likely to be due to differences in funding as well as a lack of consensus or guidelines in the literature. Access to dedicated MR for EBRT is limited in all but Sweden and Denmark, but in all countries there are financial challenges with ongoing per patient costs. Despite these challenges, significant interest exists in increasing MR guided EBRT planning over the next 5 years.